Differentiated regulation: the case of charities. (20th April 2015) - Cordery, Carolyn J.; Sim, Dalice; van Zijl, Tony
Abstract: The increasing number and influence of charities in the economy, evidence of mismanagement and the need for information for policymaking are all reasons for establishing charity regulators. Public interest and public choice theories explain charity regulation which aims to increase public trust and confidence in charities (and thus increase voluntarism and philanthropy) and to limit tax benefits to specific organisations and donors. Nevertheless, regulation is resource intensive, and growing pressure on government budgets requires efficiencies to be found. This study proposes regulation differentiated according to charities' main resource providers, to reduce costs and focus regulatory effort, and provides a feasible segmentation.